Disaster and Emergency Preparedness and the Impact of the COVID-19 Pandemic on Child Care Programs in Michigan: A Mixed-Methods Analysis. (14th April 2023) - Budnik, Elizabeth M.; Hashikawa, Andrew N.; Cator, Allison; Bradin, Stuart; Mangus, Courtney W.
Abstract: Background: Historically, the child care industry has been unprepared for emergencies. A previous study identified gaps in Michigan's child care programs' emergency plans. Study objectives were to reassess programs' preparedness plans after introduction of state-mandated emergency plans and to examine the effect of the coronavirus disease 2019 (COVID-19) pandemic on programs' operations. Methods: A 29-question survey was sent to ∼500 child care programs across Michigan in 2020 to assess emergency plans and response to COVID-19. Data were analyzed using descriptive statistics and qualitative methods. Results: A total of 346 programs (70%) responded. Most (92%) reported having a written plan, but one-third reported having no infectious outbreak plan pre-pandemic. One-third of programs lacked plans for special needs children (vs 40% in 2014); 62% lacked plans for child reunification (vs 60% in 2014); 46% reported staff received no preparedness training. COVID-19 impacted programs substantially: 59% closed, 20% decreased capacity, 27% changed disinfecting protocols. Several themes related to the pandemic's effect on programs were identified: (1) changes in learning, (2) changes in socialization, (3) increased family burden, (4) financial challenges, (5) lack of guidance. Conclusions: Significant preparedness gaps remain among Michigan's child care programs, suggesting the need for increased support and addition of emergency preparedness to programs' quality ratings.